Kesenian Arsitektur Islam: Alun-alun Kabupaten Gresik Pasca Renovasi - Abdul Wafi; Farida Novita Rahmah; Fadlilah Novia Rahmah (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
This study aims to determine the Islamic art architecture used in the Gresik Square building after renovation in 2016. This study uses qualitative research methods based on literature studies and field studies. Literature studies in this study use a journal reference written by Fikriani, Aulia (2010) entitled “Arsitektur Islam: Seni Ruang dalam Peradaban Islam” and a thesis written by Azzahra, Nofianda Fatimah (2018) entitled Konflik Pemanfaatan Ruang Publik Kota. Furthermore, the field data sources in this study uses (1) Interviews obtained from the speaker, Mr. Kris Aji, as historian and cultural observer of Gresik, (2) Observation, and (3) Documentation of the Gresik Square building after renovation. The results of this study are the Islamic architectural art used in the Gresik Square building after renovation including (1) Transfiguration of the hallway structure on the ground floor, (2) Transfiguration or ambiguity of function in open spaces decorated with date palm trees, and (3) Ornamentation with Islamic feature and style used on the second floor of the Gresik Square building fences. Overall, it can be seen that, the Gresik Square building after renovation using Islamic art architecture is used as an affirmation of Gresik's identity as an Islamic city or santri city.